A generalization of the p-series test in determining convergence or divergence of an infinite series - Lawas, Cresencia M. (Animo Repository, 2003)
Let an =ƒ(n)/g(n) whereƒ and g are polynomials of degrees r and s respectively, and r < s so that limn->oo an = 0. The traditional method in determining convergence or divergence of an infinite series of the form En 00=1 an uses the limit-comparison test where the general term an of the given series is compared with the general term of a known convergent or divergent p-series. In this paper. a much easier method called the polynomial test is presented. We also present a generalization of the polynomial test to deal with series of the form En 00=1 where f and g are not polynomial functions of n. In this case, r and s would represent the highest exponents of n in f and g, respectively.